Mao and the cultural revolution. - Hu, Angang (Silkroad Press, 2017)
Acclaimed national researcher Hu Angang presents Mao and the Cultural Revolution, an immensely rich account of the massive political event of 1966-1976 that brought seismic changes to the landscape of New China.